Heavy metals in freshly deposited sediments of the Gomati River: (a tributary of the Ganga River); effects of human activities - Singh, Munendra; Ansari, A. A.; Müller, German; Singh, I. B. (Environmental geology, 1997)
The concentrations of various metals (Cr, Cu, Co, Fe, Mn, Ni, Pb, Zn, and Cd) were determined in recently deposited surface sediments of the Gomati River in the Lucknow urban area. Markedly elevated concentrations (milligrams per kilogram) of some of the metals, Cd (0.26-3.62), Cu (33-147), Ni (45-86), Pb (25-77), and Zn (90-389) were observed. Profiles of these metals across the Lucknow urban stretch show a progressive downstream increase due to additions from 4 major drainage networks discharging the urban effluents into the river. The degree of metal contamination is compared with the local background and global standards. The geoaccumulation index order for the river sediments is Cd>Zn>Cu>Cr>Pb. Significant correlations were observed between Cr and Zn, Cr and Cu, Cu and Zn and total sediment carbon with Cr and Zn. This study reveals that the urbanization process is associated with higher concentrations of heavy metals such as Cd, Cu, Cr, Pb, and Zn in the Gomati River sediments. To keep the river clean for the future, it is strongly recommended that urban effluents should not be overlooked before their discharge into the river.